Topical anti-inflammatory effect of Ekor Naga (Rhaphidophora pinnata (L.f) Schott) leaves extract - Bernike Anatasya; Fathnur Sani K; Muhaimin Muhaimin (Pharmaciana, 2021)
Ekor Naga (Rhaphidophora pinnata (L.f) Schott) leaves are leaves that contain secondary metabolites which can be developed into medicine. Ekor Naga leaves have secondary metabolite compounds of flavonoids, alkaloids, triterpenoid saponins, steroids, tannins, and phenols. This metabolite compound is the basis for testing the anti-inflammatory effect of Ekor Naga leaves extract using topical methods. The purpose of this study was to determine the anti-inflammatory effect of the ethanol extract of Ekor Naga leaves by a topical method. This study used five treatment groups with five mice in each treatment. This research tested the anti-inflammatory activity of Ekor Naga leaves extract by using the combination of 2 methods; namely the method of forming airbags and the formation of artificial edema using the induction of 2% carrageenan solution with the observation parameters being the measurement of exudate volume and differentiation of the number of leukocyte cells observed under a microscope. The results showed that the Ekor Naga leaves extract had an anti-inflammatory effect. The best inflammatory effect is a concentration of 10%, followed by a concentration of 5% and 2.5%.